Analisis Performance Jaringan 2G Global System For MobileComunication (GSM) Frekuensi 900 MHz dan 1800 MHz Berdasrkan Data Drive Test di PT. Telkomsel Padang - Kenny Pratama Putra; Delsina Faiza; Yasdinul Huda (Universitas Negeri Padang, 2014)
This research was motivated by a decline in performance on the BTS Batang Marau, which indicates the level of Rx Level, Rx Qual and SQI not meet KPI targets, so the presence of the area around the base stations that do not meet the standard Rx Level to make phone calls (blankspot). The purpose of this study was to determine the performance of GSM 900 and 1800 networks, as well as to improve the performance of base stations Batang Marau Power Link Budget calculation method. This study discusses the improving performance of GSM network at the site decreased performance, where performance is observed through measurement results based on the data drive test. The results of data analysis showed : (1) From the analysis, GSM 1800 already meet KPI targets for Rx Level >95 %, Rx Qual >94 % and SQI >93 %. In GSM 900 results analysis and Rx Qual SQI already meet the target KPI Rx Qual >94 % and SQI >93 %, while the results of the analysis of Rx level at 09.00 already reached the target KPI >95 %, at 15:00 and 20:00, still has not reached the target KPI <95 %, which indicates the time of measurement using tools Tems Investigation, there are several areas that Rx the level of poor quality. (2) Value Rx level in the area around the base stations are <-95 dBm indicates blankspot area (can lead to a drop call). (3) The estimated increase in performance on the GSM network by the method of link power budget on the BTS Batang Marau shows 69.3 dBm Rx Level (Good quality) at a distance of 2.5 km, so it can be concluded that the performance of GSM 900 base stations have been increased Batang Marau performances.